Paratexts thresholds of interpretation - Genette, Gérard 1930-2018 (Cambridge Univ. Press, 1997)
Paratexts are those liminal devices and conventions, both within and outside the book, that form part of the complex mediation between book, author, publisher and reader: titles, forewords, epigraphs and publishers' jacket copy are part of a book's private and public history. In this first English translation of Paratexts, Gérard Genette shows how the special pragmatic status of paratextual declaration requires a carefully calibrated analysis of their illocutionary force. With clarity, precision and an extraordinary range of reference, Paratexts constitutes an encyclopedic survey of the customs and institutions as revealed in the borderlands of the text. Genette presents a global view of these liminal mediations and the logic of their relation to the reading public by studying each element as a literary function. Richard Macksey's foreword describes how the poetics of paratexts interact with more general questions of literature as a cultural institution, and situates Gennet's work in contemporary literary theory
Erscheinungsjahr des E-Books: 2009. - Literaturverz. S. 411 - 417
Keywords: Geschichte; Literature publishing / History; Discourse analysis, Literary; Authors and publishers; Transmission of texts; Criticism, Textual; Literary form; Books / Format; Paratext; Buchgestaltung; Buchtitel; Verlag; Vorwort; Inschrift; Dedikation; Anmerkung; Autor; Literatur; Hochschulschrift